A dual-amplification strategy-intergated SERS biosensor for ultrasensitive hepatocellular carcinoma-related telomerase activity detection - Shen, Kang; Hua, Weiwei; Ge, Shengjie; Mao, Yu; Gu, Yuexing; Chen, Gaoyang; Wang, Youwei (Frontiers in Bioengineering and Biotechnology, 2023)
Telomerase has been considered as a biomarker for early diagnosis and prognosis assessment of hepatocellular carcinoma (HCC), while the highly sensitive and specific methods remain challenging. In this study, a novel surface-enhanced Raman scattering (SERS) biosensor was constructed for telomerase detection using the dual DNA-catalyzed amplification strategy composed of strand displacement amplification (SDA) and catalytic hairpin assembly (CHA). This strategy relies on the extension reaction of telomerase primer induced by telomerase, forming long-stranded DNAs with repetitive sequence to catalyze the follow-up SDA event. Subsequently, the SDA products can trigger the CHA reaction between the SERS probes (hollow gold nanocages (HGNCs) modified with hairpin DNA1 and Raman reporters) and capture substrate (Au@SiO2 array labeled with hairpin DNA2), resulting in the formation of numerous “hot spots” to significantly enhance the SERS signal. Benefiting from this, the established biosensor presented excellent reproducibility, specificity and sensitivity. Moreover, ELISA was applied as the golden standard to verify the application of the proposed biosensor in real samples and the results confirmed the satisfactory accuracy of our method. Therefore, the proposed SERS biosensor has the potential to be an ideal tool for the early screening of HCC.